PENGARUH PESAN AKUN INSTAGRAM @KETIMBANG.NGEMISBEKASI TERHADAP KEPEDULIAN GENERASI MUDA - SURANTI YUNIDAR; KARTINI ROSMALAH D. K. (Institut Bisnis Muhammadiyah Bekasi, 2020)
The poverty that ensnares the elderly should get a more crucial treatment from the government. Through this account